Cost-Effectiveness of Bevacizumab Biosimilar LY01008 Combined With Chemotherapy as First-Line Treatment for Chinese Patients With Advanced or Recurrent Nonsquamous Non-Small Cell Lung Cancer - Luo, Xia; Liu, Qiao; Zhou, Zhen; Yi, Lidan; Peng, Liubao; Wan, Xiaomin; Zeng, Xiaohui; Tan, Chongqing; Li, Sini (Frontiers in Pharmacology, 2022)
Objective: To investigate whether LY01008, a locally developed bevacizumab biosimilar agent, is appropriate for widespread use among Chinese advanced or recurrent nonsquamous non-small cell lung cancer (NSCLC) patients, our current study was designed to evaluate the cost-effectiveness of first-line LY01008 combined with platinum-doublet chemotherapy versus chemotherapy alone from the perspective of the Chinese healthcare system. Material and Methods: This economic evaluation designed a Markov model to compare the healthcare cost and quality-adjusted life-year (QALY) of first-line LY01008 combined with chemotherapy versus first-line chemotherapy. Transition probabilities, including disease progression, survival, and adverse event (AE)-related discontinuation of first-line treatment, were estimated using data from the clinical trials. Costs and health utilities were derived from local databases, hospitals, and published literature. Our base case analysis and scenario analysis focused on the cost-effectiveness of chemotherapy combined with a clinical trial dosage (15 mg/kg every 3-week cycle) and a real-world dosage (7.5 mg/kg every 3-week cycle) of LY01008, respectively. Results: In the base case analysis, first-line LY01008 combined with chemotherapy was associated with an increase of 0.48 QALYs in effectiveness and an increase of CNY 189,988 (US$ 26,240) in healthcare costs compared with first-line chemotherapy, resulting an incremental cost-effectiveness ratio (ICER) of CNY 375,425 (US$ 54,430)/QALY. In the scenario analysis, first-line LY01008 combined with chemotherapy was associated with a mean healthcare cost of CNY 265,060 (US$ 38,429), resulting an ICER of CNY 221,579 (US$ 32,125/QALY) between first-line LY01008 combined with chemotherapy versus first-line chemotherapy. The parameters that determine the cost of LY01008 have the greatest impact on the cost-effectiveness results. Conclusion: From the perspective of the Chinese healthcare system, first-line LY01008 at a real-world dosage combined with chemotherapy is likely to represent a cost-effective strategy compared with first-line chemotherapy alone for Chinese advanced or recurrent nonsquamous NSCLC patients.